Less Emotion but More Fatigue: Social-Emotional Learning (SEL) Competencies, and Compassion Fatigue among Educators during the COVID-19 Pandemic - Syamsul Gultom; Dewi Endriani; Agustin Sastrawan Harahap (UNIB Press, 2022)
Driven by a qualitative study which data from individual interviews were analyzed using Malterud's systematic text condensation, this research analyzed how educators perceived Social-Emotional Learning (SEL) competencies and compassion fatigue during online teaching in the COVID-19 pandemic among 20 educators at Universitas Negeri Medan. This study discovered two emotions such as satisfaction and relief. Enjoyment of and satisfaction with teaching, contentment with teaching, and pride might all be classified as satisfaction, while sentiments of finding teaching scary, burdensome, and unpleasant, as well as a lack of technological capability, could be classified as relief. The educators also show the characteristics of compassion fatigue that have increased since the pandemic, including physical or emotional exhaustion, feelings of being overwhelmed or helpless, feelings of sadness and anxiety, and reduced empathy.